Polymorphisms in the CD14 and IL-6 genes associated with periodontal disease - Tellervo Tervonen (Blackwell Synergy, 2008)
Aim: To compare the frequencies of cytokine and receptor molecule genotypes in patients with chronic periodontitis with the corresponding frequencies in a reference population and to study the relationship between periodontal disease severity and polymorphisms in the studied genes. Subjects and methods: CD14, IL-6, TNF-a, IL-10, IL-1a, IL-1b, and TLR-4 polymorphisms of 51 periodontitis patients were studied using polymerase chain reaction. The genotype frequencies in the periodontitis patients and a reference population (n5178) were compared. Probing pocket depth (PD), periodontal attachment level (AL), and alveolar bone level (BL) were related to the genotypes. Results: No statistically significant differences could be found between the frequencies of the cytokine genotypes in the periodontitis patients and in the reference group. The extent of periodontal disease was higher in subjects with the T-containing genotype of CD14 260 and the GG genotype of IL-6 174 when compared with the extent in the rest of the group. Subjects carrying the composite genotype of the above two were most severely affected by periodontal disease. Conclusion: According to the present results, an evident association exists between the carriage of the T-containing genotype of CD14 260 and the GG genotype of IL-6 174 and the extent periodontal disease.